2022
DOI: 10.1155/2022/9039110
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-Mediated Silencing of RBP7 Promotes Breast Cancer Progression through PPAR and PI3K/AKT Pathway

Abstract: Retinoid-binding protein7 (RBP7) is a member of the cellular retinol-binding protein (CRBP) family, which is involved in the pathogenesis of breast cancer. The study aims to illustrate the prognostic value and the potential regulatory mechanisms of RBP7 expression in breast cancer. Bioinformatics analysis with the TCGA and CPTAC databases revealed that the mRNA and protein expression levels of RBP7 in normal were higher compared to breast cancer tissues. Survival analysis displayed that the lower expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…The latter gene along with ZHX2, DERL1, FAM83A and ATAD2 have been associated with intense symptoms, resistance to chemotherapy and bad prognosis of human breast cancer and metastatic canine mammary adenocarcinomas, implying interference in mammary cell growth and immune regulation (Kalashnikova et al, 2010;Klopfleisch et al, 2010;Lee et al, 2012;Fang et al, 2021;Choi et al, 2022). In accordance with the above, the suggestive significant SNP rs428540973 on chromosome 12, which was associated with SCC in Frizarta sheep, is located within RBP7; downregulation of its expression in human breast cancer has been associated with bad prognosis (Lin et al, 2022). Interestingly, the suggestive SNP for SCC on chromosome 1, rs424064526, is located within the intronic region of FSTL1, which is involved in pathogenetic pathways promoting tissue inflammation and subsequent fibrosis (Andreichenko et al, 2019;Li et al, 2021).…”
Section: Genome-wide Association Study and Gene Annotationsupporting
confidence: 56%
“…The latter gene along with ZHX2, DERL1, FAM83A and ATAD2 have been associated with intense symptoms, resistance to chemotherapy and bad prognosis of human breast cancer and metastatic canine mammary adenocarcinomas, implying interference in mammary cell growth and immune regulation (Kalashnikova et al, 2010;Klopfleisch et al, 2010;Lee et al, 2012;Fang et al, 2021;Choi et al, 2022). In accordance with the above, the suggestive significant SNP rs428540973 on chromosome 12, which was associated with SCC in Frizarta sheep, is located within RBP7; downregulation of its expression in human breast cancer has been associated with bad prognosis (Lin et al, 2022). Interestingly, the suggestive SNP for SCC on chromosome 1, rs424064526, is located within the intronic region of FSTL1, which is involved in pathogenetic pathways promoting tissue inflammation and subsequent fibrosis (Andreichenko et al, 2019;Li et al, 2021).…”
Section: Genome-wide Association Study and Gene Annotationsupporting
confidence: 56%
“…In our study, we have also observed that higher expression levels of these proteins related to HAT-1 (H3/H4, ASF-1, NASP and RBBP7) are directly correlated to a reduced survival, suggesting that this molecular network might represent an important part related to PDAC progression. The relevance of these proteins as prognostic factors for oncological patients has been demonstrated previously [33][34][35][36]. In the event of PDAC, these molecules have been shown to be implicated in a broad molecular network that facilitates pancreatic cancer progression [33,37], which may explain the association of these variables with a poor prognosis.…”
Section: Discussionmentioning
confidence: 89%